THE EFFECTIVENESS OF CAPACITY SHARING IN THE MAKASSAR HALAL INDUSTRY - Rini andriani; Wahyudin Abdullah; Murtiadi Awaluddin (Antis Publisher, 2024)
This study explores the effectiveness of capacity sharing strategies in the context of the halal industry in Makassar, with a focus on increasing operational efficiency and product innovation. Capacity sharing helps companies reduce operational costs, accelerate time to market, and drive innovation by sharing production, logistics, and R&D facilities. The capability sharing strategy has the potential to optimize the use of resources through cooperation between companies in terms of production, sales, and research and development (R&D) facilities, which can bring significant benefits in increasing the competitiveness of the halal industry.' This research uses a literature research approach that allows collecting and in-depth analysis of case studies, strategic management theory, and relevant literature covering relevant aspects of Islamic economics. This study shows that this strategy can provide significant advantages for companies in meeting stringent halal standards and facing existing operational challenges. However, to ensure the success of this strategy, challenges such as compliance with strict halal standards and collaborative risk management must be taken seriously . Capacity sharing strategies have great potential to bring positive change in the halal industry, but they must be implemented with a careful approach and supported by the right framework. The practical implications of this research include encouraging the business world and regulators to consider capacity sharing strategies as a solution to increase efficiency and innovation to maintain competitive advantage in an increasingly complex and dynamic global market.